Docking rings in a solid: reversible assembling of pseudorotaxanes inside a zirconium metal–organic framework. Issue 21 (11th May 2022) - Li, Xia; Xie, Jialin; Du, Zhenglin; Jiang, Long; Li, Guangqin; Ling, Sanliang; Zhu, Kelong
Abstract : A T-shaped ligand was designed as struts for building a zirconium metal–organic framework. Acid–base switchable docking and releasing a 24-membered crown ether inside crystals was successfully accomplished via post-synthetic modification. Abstract : An unprecedented zirconium metal–organic framework featuring a T-shaped benzimidazole strut was constructed and employed as a sponge-like material for selective absorption of macrocyclic guests. The neutral benzimidazole domain of the as-synthesized framework can be readily protonated and fully converted to benzimidazolium. Mechanical threading of [24]crown-8 ether wheels onto recognition sites to form pseudorotaxanes was evidenced by solution nuclear magnetic resonance, solid-state fluorescence, and infrared spectroscopy. Selective absorption of [24]crown-8 ether rather than its dibenzo counterpart was also observed. Further study reveals that this binding process is reversible and acid–base switchable. The success of docking macrocyclic guests in crystals via host–guest interactions provides an alternative route to complex functional materials with interpenetrated structures.